MYSTIC HERO IN SEARCH OF LIBERATION - Olson, Carl (Journal of Dharma, 1979)
ath of heroes by keeping his senses under control (Mbh. 13.142.22). The comprehension of the mystic as a hero figure is something which has not received much notice. In order to understand the mystic as a hero figure, attention must be focussed on the path of the mystic, as it shows itself in autobiographical or biographical materials. I will utilize sources from Theravada Buddhism, early Jainism, and the monistic and theistic forms of Hindu mysticism', This paper will not only attempt to show in what sense the Indian mystic is a hero figure but also to demonstrate the structure of the pattern which the mystic exhibits on his quest for liberation. Lastly, I will attempt to suggest in what sense the mystic is a creative cultu